Effect of athletics in the development of some physical abilities, ages 11-12 years - Talaat Hussein, Feris (Journal of Physical Education, 2012)
That the practice of athletics for children and outdoor halls closed or in the school grounds help in the development of physical abilities is no room for doubt that the possession of the individual to these capabilities lead to strengthening the body and keep him out of diseases, hence the importance of research in the preparation of the field of the proposal in which you can develop some physical capacities of children, and research aims to prepare the field of developmental athletics for children ages 11-12 years, and has used the researcher the experimental method on a sample of elementary school students for the year Aldarcy 2011-2012 and the 24 students, have formed the percentage of the sample (7.25%) of the total, and emerged through the results of research show that the preparation of the field and divided into areas and helped limit the contests in which the research sample in the development of some physical abilities